"TEKA-TEKI SILANG BAHASA INDONESIA: ANALISIS SATUAN KEBAHASAAN DAN RELASI MAKNA" - , DEVI RAHMI; , Wira Kurniawati, S.S, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to describe the linguistic units of questions and answers at crossword in indonesian and expose the relation of meaning contained in it. In this case, the linguistic units in the questions and answers are not the same and it's make interesting to researched the difference. In addition, there are relations of meaning between questions and answers, that can be examined through the theory of the relation of meaning. The research consists of three stages, namely the provision of data, data analysis, and presentation of the results of the data analysis. Data source in this research[is book of Crossword of Kompass Choice bind 2, brief by TTSPK. The provision of the data is done by the method of observational and applied with nonparticipation observation as a subsequent technique for analysis linguistic units and relationships. Data analysis of linguistic units and relations of meaning (internal language) performed by the distributional method and applied with direct element technique, as for the analysis of the relation of meaning (external language) is done with equal method and applied with referential equal technique. Presentation of the results of the data analysis formally by presenting charts and informally to describe the results of the analysis in plain words that easily understood reader. The results showed that linguistic units in question are word, phrases, and sentence, while in answer is only word. That is because the question is guidance function or keyword so that not all the instructions or keyword can describe something with just a word. In TTSPK, there are sinonimi, antonimi, hiponimi, and referential. The result of comparison analysis indicate that the referensial more predominating than other relations.